2008
DOI: 10.1002/app.29413
|View full text |Cite
|
Sign up to set email alerts
|

Crystallization, mechanical, and rheological behavior of polyvinylidene fluoride/carbon nanofiber composites

Abstract: Composites of polyvinylidene fluoride (PVDF)/carbon nanofibers (CNFs) with different nanofiber contents were prepared by melt-blending using a twinscrew extruder by directly mixing CNFs with PVDF in the molten state. Fibers were extruded from the blended pellets. CNFs improved the nucleation efficiency of PVDF but the percent crystallinity decreased with increasing CNF concentration. X-ray diffraction results showed a change in the a phase, but the transition to the b phase did not occur. Dynamic mechanical an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
30
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(38 citation statements)
references
References 18 publications
8
30
0
Order By: Relevance
“…The corresponding increase in the storage modulus ( G ′), is higher than that for loss modulus G ″. It has been reported that the difference between storage modulus of nanocomposites and pure PU is higher at low frequencies, which agrees well with our result where the effect of MWNT loading is much higher at low frequencies. As reported by Vidhate et al ., this behavior can be attributed to different dominant mechanisms of storage modulus enhancement at low and high frequency regions.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…The corresponding increase in the storage modulus ( G ′), is higher than that for loss modulus G ″. It has been reported that the difference between storage modulus of nanocomposites and pure PU is higher at low frequencies, which agrees well with our result where the effect of MWNT loading is much higher at low frequencies. As reported by Vidhate et al ., this behavior can be attributed to different dominant mechanisms of storage modulus enhancement at low and high frequency regions.…”
Section: Resultssupporting
confidence: 93%
“…It has been reported that the difference between storage modulus of nanocomposites and pure PU is higher at low frequencies, which agrees well with our result where the effect of MWNT loading is much higher at low frequencies. As reported by Vidhate et al ., this behavior can be attributed to different dominant mechanisms of storage modulus enhancement at low and high frequency regions. Dimensionally stable carbon nanotube as reinforcement increases the storage modulus at low frequency while, it may control the elastic behavior of the PU as polymer matrix at higher frequencies.…”
Section: Resultssupporting
confidence: 77%
“…P(VDF-TrFE) is a semi-crystalline thermoplastic polymer with excellent process ability, high mechanical strength, high dielectric permittivity and thermal stability. But its degree of crystallinity was affected by filling it with nanoparticles like carbon nanofiber (CF) [14], carbon nanotubes (CNTs) [15] or nanoclays [16,17]. The mechanical properties are directly linked to the crytallinity ratio.…”
Section: Introductionmentioning
confidence: 99%
“…30 The mobilization of the amorphous phase of the matrix is significantly restricted by the spatial orientation of nanofibers, which prevents the dynamic deformation of matrix as a result the stiffness of TPU increases substantially. 31 Figure 10(b) represents typical tear test stressstrain diagrams of the neat TPU and its nanocomposites. Table III shows that the tear strength of the TPU/CNF nanocomposites substantially increases at first up to 10 wt % CNF loading and then decreases at 15 wt % CNF content but still the tear strength is higher than that of neat TPU.…”
Section: Mechanical Propertiesmentioning
confidence: 99%